Cyberpolitics in international relations - Choucri, Nazli (MIT Press, 2012)
An examination of the ways cyberspace is changing both the theory and the practice of international relations. Cyberspace is widely acknowledged as a fundamental fact of daily life in today's world. Until recently, its political impact was thought to be a matter of low politics - background conditions and routine processes and decisions. Now, however, experts have begun to recognize its effect on high politics - national security, core institutions, and critical decision processes. In this book, Nazli Choucri investigates the implications of this new cyberpolitical reality for international relations theory, policy, and practice. The ubiquity, fluidity, and anonymity of cyberspace have already challenged such concepts as leverage and influence, national security and diplomacy, and borders and boundaries in the traditionally state-centric arena of international relations. Choucri grapples with fundamental questions of how we can take explicit account of cyberspace in the analysis of world politics and how we can integrate the traditional international system with its cyber venues. After establishing the theoretical and empirical terrain, Choucri examines modes of cyber conflict and cyber cooperation in international relations ; the potential for the gradual convergence of cyberspace and sustainability, in both substantive and policy terms ; and the emergent synergy of cyberspace and international efforts toward sustainable development. Choucri's discussion is theoretically driven and empirically grounded, drawing on recent data and analyzing the dynamics of cyberpolitics at individual, state, international, and global levels.
Keywords: Internet and international relations.; Technology and international relations.; Internet -- Political aspects.; Information technology -- Political aspects.; Internet et relations internationales.; Technologie et relations internationales.; Internet -- Aspect politique.; Technologie de l'information -- Aspect politique.; POLITICAL SCIENCE -- Globalization.; COMPUTERS -- Information Theory.; Information technology -- Political aspects; Internet and international relations; Internet -- Political aspects; Technology and international relations; Internationale Politik; Cyberspace; Internet; Informationstechnik; SOCIAL SCIENCES/Political Science/General